Influence of fatty acid composition on contact angle and wear rate of Jatropha curcas and sunflower’s mixture by varying compositions mixture - Ma’arif, Moch. Syamsul; Wardana, I Nyoman Gede; Darmadi, Djarot B.; Novareza, Oyong; Admantara, Nanu; Aisyah, Iis Siti (Eastern-European Journal of Enterprise Technologies, 2024)
United Nation Sustainable Development Goals make sustainability become common goals which drives into investments of innovative product and technology focusing on sustainability. Cutting oils are generally made from mineral oil and the renewable replacement is sought after and one of them are Jatropha curcas and sunflower oil or blend of them. Viscosity and adsorption will influence the properties of cutting oil. The study concern on the relationship between percentage of JCO in the mixture to anti-wear properties and contact angle measured using goniometer contact angle and pin-on-disk tribometer by varying percentage of Jatropha curcas oil in mixtures for 2.5 %, 5 %, 10 %, 20 %, and 30 %. Also, molecular simulation is conducted through molecular dynamic in search of dipole moment, electrostatic potential, polarizability and bond energy. The approach is employed to connect molecular interaction and non-linearity trending of experiment. The experiment shows contact angle and wear scar width and also wear rate become higher when percentage of Jatropha curcas oil is higher. The lowest contact angle is 26.9 deg. and the highest is 36.9 deg. of 2.5 % and 30 % Jatropha oil. The highest wear rate is 6.77e-7 and the lowest is 2.74e-7 of 2.5 % and 30 % Jatropha oil. The simulation gives supporting basis in the finding of experiment in which the viscosity is more prominent in governing wear rate than adsorption. Increases of Jatropha curcas percentages have inversely proportional to dipole moment, polarizability, electrostatic potential and bonding which explain why the fatty acids become more adhere to the fatty acid than to surface. The finding is restricted only for idealized conditions both of molecular structure and surface.